Polymyalgia Rheumatica and Seronegative Elderly-Onset Rheumatoid Arthritis: Two Different Diseases with Many Similarities - Ciro Manzo; Amir Emamifar (European Medical Journal, 2019)
Polymyalgia rheumatica (PMR) and seronegative elderly-onset rheumatoid arthritis (SEORA) are two of the most frequent inflammatory rheumatologic diseases in elderly patients. At first presentation, there are many similarities between PMR and SEORA, that may lead to a real diagnostic conundrum. The most relevant similarities and differences between PMR and SEORA are discussed in this review. In addition to the acute involvement of the shoulder joints, important features characterising both diseases are morning stiffness longer than 45 minutes, raised erythrocyte sedimentation rate, and a good response to low doses of prednisone. Some findings (such as erosive arthritis or symmetrical involvement of metacarpophalangeal and/or proximal interphalangeal joints) can help to make the diagnosis of SEORA, whereas shoulder and hip ultrasonography and 18-FDG PET/CT seem to be less specific. However, in several patients only long-term follow-ups confirm the initial diagnosis. A definite diagnosis of PMR or SEORA has significant therapeutic implications, since patients with PMR should be treated with long-term glucocorticoids, and sometimes throughout life, which predisposes the patients to serious side effects. On the contrary, in patients with SEORA, short-term treatment with glucocorticoids should be considered when initiating or changing disease modifying antirheumatic drugs, followed by rapid tapering.